The IPU Resolution on Women’s and Children’s Health: An Initial Framework for Accountability Reporting - Inter-Parliamentary Union; Inter-Parliamentary Union (2013)
This report highlights the results from the first review of parliamentary efforts in implementing the IPU resolution of April 2012: ‘Access to health as a basic right: The role of parliaments in addressing key challenges to securing the health of women and children.’